The Influence of Concentration Chitosan of A Shell Snail to Lower Levels of BOD and COD on Waste Laundry - Kasmudin, Karim; Fitria, Fitria; Artiningsih, A. (PT Mattawang Mediatama Solution, 2022)
Disposal of laundry waste directly in the river is the cause of high river pollution. Laundry wastewater resulted in an increase in BOD and COD parameters so that it had a negative impact on ecosystem life. The coagulation process using chemicals can reduce BOD and COD parameters in wastewater but have negative effects on health. Chitosan from snail shells can be used as an alternative coagulant that is environmentally friendly because it contains about 70% - 80% chitin. This study aims to synthesize chitosan biocoagulants from snail shells and to test the effectiveness of snail shell chitosan in the treatment of laundry wastewater. Fourier Transform Infra-Red (FTIR) analysis showed that the deacetylation rate of chitosan obtained was 78.06%. Coagulation was carried out on wastewater using variable concentrations and stirring speed. The results showed that the optimum dose of snail shell chitosan biocoagulant was at a concentration of 0.4%. At this dose, the coagulant can bind to the most optimal contaminants so that it can reduce the BOD and COD values ​​in laundry waste and the Fast Stirring Speed ​​of 100 rpm is the optimum stirring speed because large speeds will produce excessive shear forces and prevent the desired floc arrangement.